2022
DOI: 10.1039/d2cc02724k
|View full text |Cite
|
Sign up to set email alerts
|

A polyaniline surface-modified Prussian blue analogue cathode for flexible aqueous Zn-ion batteries

Abstract: Aqueous Zn-ion batteries have gained popularity due to their low cost and high safety, but their low energy density limits application scenarios. Although the Prussian blue analogue (PBA) has the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…reported a spring‐like FQAZIB with the maximum stretch rate as high as 600% (Figure 6d). [ 106 ] Figure 6d shows the galvanostatic charge–discharge (GCD) curves of the prepared FQAZIB under various tensile strains, which suggested that the battery possesses the ability of providing a stable energy supply at various strains. Depositing active materials on stretchable current collector forming microcracked structure is also regarded as a promising method to fabricate stretchable FQAZIBs.…”
Section: Functional Strategies Of Fqazibsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported a spring‐like FQAZIB with the maximum stretch rate as high as 600% (Figure 6d). [ 106 ] Figure 6d shows the galvanostatic charge–discharge (GCD) curves of the prepared FQAZIB under various tensile strains, which suggested that the battery possesses the ability of providing a stable energy supply at various strains. Depositing active materials on stretchable current collector forming microcracked structure is also regarded as a promising method to fabricate stretchable FQAZIBs.…”
Section: Functional Strategies Of Fqazibsmentioning
confidence: 99%
“…Reproduced with permission. [ 106 ] Copyright 2022, Royal Society of Chemistry. e) Schematic illustration of stretchable FQAZIB.…”
Section: Functional Strategies Of Fqazibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rechargeable aqueous batteries are attracting increasing attentions due to their low cost, high safety, environmentally friendly nature, and improved rate performance, the "free water" (the term "free water" indicates water molecules interacting solely with other water molecules) [139] molecules in aqueous electrolytes strongly limit the electrochemical stability window of the electrolyte and trigger multiple side reactions, thus affecting cell performance upon cycling. In order to suppress the activity of "free water" molecules and expand the electrochemical stability window, novel electrolytes and components have been proposed, including high concentrated electrolytes or "water-in-salt/gel" electrolytes, [78,82,87,95,97,105,107,140] hybrid electrolytes, [65,66,74,75,77,78,[81][82][83]85,87,95,107,141,142] solid polymer electrolyte, [103] and additives, [84,86,88,89] to improve the electrochemical performances of AZIBs. D. Kim et al [140] reported that the cycling performance of ZnHCF in concentrated electrolyte (3 M Zn(NO 3 ) 2 ) was superior to that observed in the diluted system (1 M Zn(NO 3 ) 2 ), as a consequence of the decrease in the hydration number and radius of the zinc ions in the concentrated electrolyte.…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…[1][2][3][4] In this regard, aqueous zinc-ion batteries (ZIBs) have recently received attention due to their intrinsic advantages, including high safety, low cost, and environmental friendliness. [5][6][7][8][9][10] Different types of cathode materials, including manganese oxides, [11][12][13][14][15] vanadium oxides, [16][17][18][19][20][21] Prussian blue analogs, [22][23][24] and even organic cathodes, [25][26][27] have been widely utilized in the ZIBs, among which, vanadate-based cathodes, especially V 2 O 5 -originated species, have been extensively studied. Specically, because of the multivalent property, the open layered structure, and the support from the intercalated cations, V 2 O 5 -based materials can store more Zn 2+ to provide higher capacity.…”
Section: Introductionmentioning
confidence: 99%